Analisa Faktor Internal dan Perencanaan Operasional pada Bisnis Plan Swipewash Marketplace untuk Layanan Laundry - Tasya Yultavera; Dimas Negoro; Unggul Kustiawan; Ferryal Abadi (Yayasan Literasi Sains Indonesia, 2025)
The e-commerce industry in Indonesia is experiencing rapid growth, supported by a large population, a growing middle class, and increasing internet penetration. In 2023, Indonesia's e-commerce transaction value will reach USD 62 billion, with the number of users projected to reach 99.1 million by 2029. This potential drives new opportunities, including daily necessities such as laundry, bag spa, and shoe spa. In a busy urban society, these services are an important need. Digital platforms can provide solutions with easy access, transparency, and efficiency for consumers. Customers face challenges such as concerns about the safety of goods, difficulty in comparing prices, and limited operational hours. In analyzing internal factors, SwipeWash uses a strategic approach to identify the company's strengths and weaknesses and opportunities to increase competitiveness in the e-commerce laundry service industry. Customer demand analysis is the main focus in understanding the growing market needs. SwipeWash offers services that guarantee the safety of customers' personal belongings, provide ease of price comparison, and ensure comfort with services available 24 hours a day.